Effect of Different Watering Regimes on Agromorphology of Selected Coffee Genotypes - Gichimu, Bernard M.; Cheserek, J. J; Mushimiyamana, D.; King’oro, M. W. (SCIENCEDOMAIN international, 2014)
Aims: The aim of this study was to determine the effect of different watering regimes on selected coffee genotypes and to evaluate drought tolerance among selected coffee genotypes. The study also aimed at determining the optimum watering interval for these genotypes under high temperature conditions. Study Design: Completely Randomized Design (CRD) with 3 replications. Place and Duration of Study: The experiment was conducted in a greenhouse at Coffee Research Station in Ruiru, Kenya between October and December 2012. Methodology: A total of 11 coffee genotypes were used in this study. These comprised of Coffea canephora (Robusta), one wild accession and nine Coffea arabica genotypes. Six months old seedlings of the test genotypes pre-germinated and transplanted in black polythene bags were obtained from the Coffee Research Station experimental nursery. The seedlings were placed on raised benches in the green house and each potted seedling represented a plot. The seedlings were watered with 0.3 liters of water per pot at six watering regimes applied as follows: watering after every 2 days, 4 days, 7days, 14days, 21 days and no watering at all. Morphological data on leaf number, number of nodes and plant height were recorded at the start of the experiment and after every 7 days until termination of the experiment. Root to shoot biomass ratio was also computed as percentage at the end of experiment. The data were subjected to analysis of variance (ANOVA) at 5% level of significance. Least Significance Difference (LSD5%) was used to separate the means. Results: Significant difference on change in leaf number, number of nodes, plant height and percent root: shoot biomass was observed among the genotypes. Growth was found to decrease as water stress increased. Conclusion: It was concluded that there is a potential for selection for drought tolerance from a diverse population of coffee genotypes. The most promising genotypes were West Pokot accession and tall Arabica genotypes such as SL34.
Keywords: coffee; drought; High Temperatures; Kenya